A low cost corn seed planting machine / Muhamad Fauzi Othman ... [et al.] - Othman, Muhamad Fauzi; Saedon, Juri; Meon, Mohd Suhairil; Husain, Hazran; Mohd Shawal, Mohd Syahar (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
In rural areas, the corn planting method is still using traditional method and labor intensive. Available machine in the market is too expensive and not competitive for small scale corn field. Traditional method is not only time consuming, but also inconsistent in terms of seed planting distance. These problems encourage a proper, cheap and effective method to be studied and developed in this project. The aim of this project is to develop a corn seed planting machine for small scale corn field that could improve the way of planting the corn seed. Several concepts were generated and evaluated in designing the machine and a prototype of the machine was fabricated. The result shows that the distance between holes, depth of holes and numbers of seed per hole is consistent and acceptable.